Physicochemical, Functional, and Antioxidative Characteristics of Oyster Mushrooms - Alona Tiupova; Remigiusz Olędzki; Joanna Harasym (Applied Sciences)
Oyster mushrooms (Pleurotus species) have gained significant attention in food science and nutrition due to their exceptional nutritional and functional properties. This review examines various oyster mushroom species’ comprehensive physicochemical characteristics, functional attributes, and antioxidative properties. Through analysis of current literature, we establish that oyster mushrooms contain substantial amounts of protein (15–30%), carbohydrates (43–60%), dietary fibre, and essential micronutrients while maintaining low-fat content (~1.2%). The mushrooms demonstrate significant antioxidant activity through compounds such as ergothioneine, phenolics, and flavonoids, with different species showing varying levels of bioactive compounds. Scientific studies reveal that processing methods, particularly different drying techniques, significantly impact their nutritional composition and functional properties. Notable findings include the identification of specific compounds in coloured varieties, such as pink chromoprotein in Pleurotus djamor and various melanin types, which contribute to both aesthetic and functional properties.